Analytical Validation and Clinical Utilization of the Oncomine Comprehensive Assay Plus Panel for Comprehensive Genomic Profiling in Solid Tumors - Catherine I. Dumur; Ramakrishnan Krishnan; Jorge A. Almenara; Kathleen E. Brown; Kailyn R. Dugan; Christiana Farni; Fatima Z. Ibrahim; Naomi A. Sanchez; Sumra Rathore; Dinesh Pradhan; Jonathan H. Hughes (MDPI AG, 2023)
The detection of driver oncogenic variants and the recent identification of tumor-agnostic genomic biomarkers has driven the use of comprehensive genomic profiling (CGP) for disease diagnosis, prognosis, and treatment selection. The Oncomine™ Comprehensive Assay Plus (OCA+) panel uses DNA and RNA to detect single nucleotide variants (SNVs), small insertions/deletions (Indels), and structural variants (SVs) across 501 genes. Moreover, microsatellite instability (MSI), tumor mutational burden (TMB), and homologous recombination deficiency (HRD) status are assessed in a single workflow. Herein, we present the analytical validation and clinical utilization of OCA+. By using commercial reference materials, we found good analytical sensitivity, specificity, and precision for all biomarkers analyzed. The limit of detection (LoD) was validated for SNVs and Indels at 4%, except for Indels located in homopolymeric regions, where the LoD was 10%. An additional set of 81 tumor samples, including cytology smears, were sequenced to assess the clinical utility of the OCA+ across different tumor types. Among the clinical cohort, OCA+ demonstrated 100% accuracy, sensitivity, and specificity for all biomarkers analyzed, except for MSI assessment of endometrial cancer cases, where 83% accuracy and 67% sensitivity were achieved, compared to PCR and IHC. The validation of accuracy and robustness of this assay supports the OCA+'s utility for solid tumor CGP.